Optimization of process parameters with the Taguchi Method for best build time and surface quality - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Sharum, Mohamad Afiq (Penerbit Universiti Kebangsaan Malaysia, 2025)
Taguchi Method is a valuable tool that has been introduced to optimize the quality of products or processes. It effectively identifies the optimal combination with a minimal number of experiments. In the case of parts printed with Fused Deposition Modeling printers, the outcomes vary depending on changes in the printer process parameters, such as build orientation, layer thickness, and raster angles. This study focused on samples produced using Stratasys FDM 400 FDM 3D printer, evaluating their build time and surface roughness performance. To achieve optimal performance, the Taguchi Method was applied. For this project, an L9 (33) orthogonal array was employed, involving 9 sample pieces printed with ABS-M30i material to assess three parameters, namely build orientation, layer thickness, and raster angles, each at three different levels. The samples (mounting bracket) were designed with SolidWorks. They were then evaluated for build time and tested for surface roughness using the Mitutoyo Surftest SJ 301. The resulting data was analyzed, revealing that the samples with an XY orientation, a layer thickness of 0.33 mm, and a raster angle of 90° achieved the shortest build time. Conversely, the samples with an XY orientation, a layer thickness of 0.18 mm, and a raster angle of 30° demonstrated the lowest average surface roughness (Ra value). These findings indicate that the properties of samples produced with the Stratasys FDM 400 MC printer vary depending on the combination of process parameters.